Optimal Recovery of Base Metals from Waste Slag in the Laboratory DC Arc Furnace - W. Banda; N. T. Beukes (International Mineral Processing Congress, 2003)
Recovery of Co from slag is a recent advancement in the extractive metallurgy of nonferrous metals. In this study a DC arc technology at laboratory scale has been applied to investigate the selective recovery of Co from slag, under three different flux types with an emphasis on influencing the activity of FeOx, SiO2 and CoO in the slag. It is known that reduction of slag by carbon is only up to a certain level after which, the recovery will depend on the chemistry of the slag, hence the need to modify the slag chemistry. Two power settings were employed to induce higher temperatures and aggressive agitation. The results were interpreted by comparing how much Co and Fe was in the slag and alloy. TiO2 reduced the amount of Fe in the product alloy compared to when CaO and CaF2 were used. The change in power did not seem to have had a major effect on the recovery although the amount of material lost to flue dust was more at a higher power rate.